ANALISIS PENOKOHAN PADA TOKOH DEDI PADIKU MENGGUNAKAN PENDEKATAN PSIKOANALISIS DALAM NOVEL “MENGEJAR-NGEJAR MIMPI” - Elsa Karlina; Cacu Zaenudin; Aditya Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the limited novel " Mengejar-Ngejar Mimpi " by my masterpiece rich in motivation which reviews the story of a dedi in me who wants to achieve his dream of becoming a novelist. This research was formulated for the psychoanalytic approach. Psychoanalysis focuses on the subconscious world and is not limited to the world of the conscious mind. This research aims to describe and explain typical, funny, tragic, and inspiring knowledge, walking with one person at a time. This study used descriptive qualitative research using content analysis. This method is used to examine the contents of a document. The document in the research novel "chasing dreams" by Dedi Padiku. The results of the study show that someone who is serious in achieving a dream by continuing to work carefully, never giving up, not easily discouraged, will bring him into a novelist.